2010
DOI: 10.1098/rsif.2010.0541
|View full text |Cite
|
Sign up to set email alerts
|

Dual-resolution molecular dynamics simulation of antimicrobials in biomembranes

Abstract: Triclocarban and triclosan, two potent antibacterial molecules present in many consumer products, have been subject to growing debate on a number of issues, particularly in relation to their possible role in causing microbial resistance. In this computational study, we present molecular-level insights into the interaction between these antimicrobial agents and hydrated phospholipid bilayers (taken as a simple model for the cell membrane). Simulations are conducted by a novel 'dual-resolution' molecular dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 88 publications
(185 reference statements)
4
60
0
Order By: Relevance
“…SSD is a model consisting of a Lennard-Jones sphere, a point dipole, and an additional octupolar term aimed at reproducing hydrogen bonding. SSD has been used to study liquid water and ice [80][81][82][83], and as a solvent in various systems [80,[84][85][86][87][88][89]. In Table 7 we collect results obtained from various slightly different parametrisations of the SSD force field reported in the literature; good agreement with the experiment can be noticed in terms of bulk properties.…”
Section: Comparison Between Elba and Othersupporting
confidence: 63%
“…SSD is a model consisting of a Lennard-Jones sphere, a point dipole, and an additional octupolar term aimed at reproducing hydrogen bonding. SSD has been used to study liquid water and ice [80][81][82][83], and as a solvent in various systems [80,[84][85][86][87][88][89]. In Table 7 we collect results obtained from various slightly different parametrisations of the SSD force field reported in the literature; good agreement with the experiment can be noticed in terms of bulk properties.…”
Section: Comparison Between Elba and Othersupporting
confidence: 63%
“…Bereau and Kremer (2015) showed that MD simulations with coarse-grained models can lead to free energy profiles that are similar to those obtained by allatom simulations [99]. There are also a number of studies that use a dual-resolution model, where the lipid membrane and the water are simulated using a coarse-grain model, and the drugs, such as β-blocker drugs and antibiotics, are simulated using an atomistic model [100,101]. However, in this review, the focus will be on all-atom MD simulations.…”
Section: Accepted Manuscriptmentioning
confidence: 81%
“…For example, the permeability was correlated with the permeate size [234], reference solvents [234,235], and free energy barriers [100,101]. Furthermore, cellular automata models have been developed for estimating the membrane permeability of drugs [236,237].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Different from the unitless binding constant K bind (eq 1) calculated from our simulations, experimentally determined partition coefficients are usually reported as K a = [P] mem /[L][P] aq , where [L] is the concentration of the total lipid. To facilitate a comparison between our simulation with experimental data, we follow the simple correction provided by Tzlil et al 43 (30) where N A is Avogadro's number, a L is the average area per lipid of the membrane (70 Å 2 ), and λ is the membrane bilayer thickness (including the surrounding water, typically 86.6 Å). This leads to…”
Section: ■ Computational Methodsmentioning
confidence: 99%